Surgical Competency for Robot-Assisted Hysterectomy: Development and Validation of a Clinical Assessment Tool. (October 2016) - Frederick, Peter; Szender, James; Aly, Ahmed
Abstract : BACKGROUND: The purpose of this study was to develop and utilize a clinical assessment tool to objectively measure robotic surgical skills and facilitate robotic surgery training and education. METHODS: This was a two-phase study. In phase I, the critical elements of a robotic hysterectomy were deconstructed into 6 key domains to assess technical skills for procedure completion. For each domain, anchor descriptions were developed to match a 5-point Likert scale. Delphi methodology was used for content validation. A panel of five expert robotic surgeons refined this scoring system using the Content Validity Index. In phase II, surgeons with varying degrees of experience performed a robotic hysterectomy. Video recordings were evaluated by blinded expert reviewers using the above scoring system. Descriptive statistics were evaluated for the total scores as well as each domain. Tests of both inter-rater (agreement between the assessors) and test-retest (consistency of scoring over time) reliability were performed with a threshold of significance at P <.05. RESULTS: Videos from 16 robotic hysterectomies, with two surgeons evaluated per case, were reviewed by the expert panel. The score for all surgeons was 4.36±0.49 (mean±SD). Scores varied according to surgical domain under assessment, however globally there was no difference between scores for trainees or attendings ( P =.83). There was excellent agreement between raters with respect to score in two domains, while disagreements occurred with respect to the other domains. DISCUSSION: This pilot study demonstrates the feasibility of utilizing a standardized rubric for clinical skills assessment in robotic hysterectomy.